Implementation Of Broadband Technology Infrastructure Using Techno-Economic Analysis ( A Casa At The Goverment Of West Java Province) - Rambung, Richard A.; Sembiring, Ryan Johan; Surjati, Indra; Mandagi, Albert (Teknik dan Ilmu Komputer, 2017)
This research is to identify the economic value of implementing fixed-WIMAX (Worldwide Interoperability for Microwave Access) technology and customized fiber-optic technology in the development planning of broadband infrastructure owned by the government of West Java Province. This research is descriptive, and using Techno Economic Analysis. The result shows ratio of the values of technology investments to the value of revenue assumption in government user or non-government user. It is seen that the capital expenditure (CAPEX) value for technology investment of fixed-WIMAX and fiber-optic are US13,900,660 and US18,297,880. Meanwhile, the operational expenditure (OPEX) value are US8,459,280 and US1,646,530. The Net Present Value (NPV) for fixed-WIMAX and fiber-optic technology implementation projected for five years is US14744,52 and US22,918,470. It can be concluded that investment project is feasible, but fiber-optic technology investment is more profitable. If a review based on Internal Rate of Return (IRR) calculation shows that fixed-WIMAX or fiber-optic technology implementation gives the same value, which is 30.6%, it can be concluded that both implementations are feasible.ÃÂ Keywords: West Java, fixed-WIMAX, fiber-optic, techno-economic.ÃÂ